Prediction of recycle method using relevance vector machine - Mat Noor, Muhamad; A/L Kadirgama, Kumaran; Rahman, Md. Mustafizur; Maleque, Md. Abdul (Trans Tech Publications, Switzerland, 2011)
Life cycle engineering is the engineering and design of products and processes to minimize the cost and environmental impact for the life cycle phases of a product. Relevance Vector Machine method (RVM) is used to determine recycling strategy (reuse, service, remanufacture, recycle with disassembly, recycle without disassembly and disposal). Seven parameters (wear – out life, technology cycle, level of integration, number of parts, reason for redesign and design cycle) were considered as the input for the RVM model. Three electronic equipments were selected to be examined such as vacuum cleaner, washing machine, television. All the results verify previous literature study. The prediction model predicts the end of life (EOL)strategies quite closely with real industry practices.